Design of multi-frequency CW radars - Jankiraman, Mohinder (SciTech Publishing, 2007)
The book is organized into three parts. This first part covers the basic CW radar theory. The second part introduces the reader into how this theory is utilized in the design of an actual radar called Calypso. The third and final part discusses the theory and design of a more complex multifrequency CW radar called the PANDORA. The PANDORA radar yields extremely high resolutions even for CW radars and has found many applications, the first being in its use as a ground penetrating radar (GPR) for landmine detection, an area where extremely high resolutions are vitally required. Moreover, the architecture of the PANDORA radar is such that it can also be applied to pulsed radars and is not just confined to CW radars. Hence, it is expected that this type of radar will find wide application.